2011
DOI: 10.4161/nucl.2.2.15209
|View full text |Cite
|
Sign up to set email alerts
|

Binding kinetics of human ISWI chromatin-remodelers to DNA repair sites elucidate their target location mechanism

Abstract: Chromatin remodelers translocate nucleosomes along the DNA chain in an ATP-dependent manner. This catalytic activity is particularly important for DNA replication and repair since both processes require a significant amount of nucleosome translocations and assembly during DNA synthesis. Recently, we have studied the mobility and interactions of the human ISWI family chromatin remodelers Snf2H and Snf2L as well as Acf1, one of the non-catalytic subunits present in the ACF and CHRAC complexes of Snf2H. We propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 38 publications
5
44
0
Order By: Relevance
“…This is consistent with the distinct biochemical modes of action of Brg1 and Snf2h ATPases (Erdel and Rippe, 2011;Kadam and Emerson, 2003;Khavari et al, 1993;Narlikar et al, 2002;Tang et al, 2010;Toiber et al, 2013). The role of Snf2h in lens differentiation is related to its recently established function in the control of Purkinje and granule cell progenitor proliferation during cerebellar development (Alvarez-Saavedra et al, 2014).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This is consistent with the distinct biochemical modes of action of Brg1 and Snf2h ATPases (Erdel and Rippe, 2011;Kadam and Emerson, 2003;Khavari et al, 1993;Narlikar et al, 2002;Tang et al, 2010;Toiber et al, 2013). The role of Snf2h in lens differentiation is related to its recently established function in the control of Purkinje and granule cell progenitor proliferation during cerebellar development (Alvarez-Saavedra et al, 2014).…”
Section: Discussionsupporting
confidence: 60%
“…*P≤0.05 ( paired Student's t-test), cDNA control vector versus Pax6 and/or Hsf4 cDNA. chromatin remodeling participates in DNA repair (Erdel and Rippe, 2011;Lans et al, 2012;Zhang et al, 2009). SWI/SNF complexes are known to be recruited to phosphorylated H2AX via the interaction between the Brg1 bromodomain and acetylated lysines in histone tails (Lee et al, 2010).…”
Section: Kip2mentioning
confidence: 99%
“…The slower Snf2H-GFP displayed a distribution that is elongated along the time axis and shortened along the spatial axis compared with the distributions for GFP and RFP. This reflects that Snf2H-GFP requires more time to translocate a given distance than GFP/RFP or GFP 5 , and that fewer molecules reach more distant pixels within the frame time τ f . The measured translocation probability distributions can readily be evaluated by visual inspection and compared with exemplary theoretical maps for pure diffusion or reaction-diffusion processes with the parameters determined by the profile-fitting analysis described in the next section (diffusion model and reaction-diffusion model in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This appears to be a general feature required for an efficient search process of factors that need to find specific sites on chromatin as discussed in a number of reviews (1)(2)(3). Such a "continuous sampling" type of target location mechanism is characteristic for imitation switch (ISWI) chromatin remodelers as concluded from our previous analysis (3)(4)(5). The ISWI family consists of two ATPases, Snf2H and Snf2L, in humans, which assemble into different complexes via association with additional subunits (6,7).…”
mentioning
confidence: 92%
“…47 The accessibility of DNA repair enzymes to damaged DNA is blocked by nucleosomes, thus chromatin remodeling must occur during the detection and repair of damaged DNA. 48,49 Indeed, we found that the 'unique p53LOH' list contains the chromatin remodeler Smarca1, which belongs to the ISWI ATP remodeling family. 36 In summary, we present for the first time the evidence for a physiological bi-directional p53LOH process, which may serve as a cell fate checkpoint in SCs.…”
Section: Discussionmentioning
confidence: 99%